Impact of a University Alcohol Policy Change on Bystander Responses to Alcohol-Related Medical Emergencies. (December 2018) - Haas, Amie L.; Welter, Nicholas C.
Two studies evaluated the implementation of a stricter campus underage drinking policy on service utilization and bystander helping behaviors for alcohol-related medical emergencies. A program evaluation (Study 1) examined campus emergency medical service logs assessing changes in call volume and service utilization, finding a 30% reduction in call volume postpolicy change. Study 2 provided a qualitative data summarizing campus first responder ( N = 35) accounts of off-duty alcohol-related emergency calls. Off-duty calls increased postpolicy change and thematic analyses indicated they were (a) motivated by fear of campus sanctions, (b) often yielded delays or failures to contact campus emergency staff, and (c) resulted from student misunderstandings of policy implications for bystander helpers. Findings highlight potential challenges in executing environmental strategies to reduce college drinking.